Getting things done through people (Waterford, CT. : Bureau of Business, 1989)
Getting people to co-operate is a vital skill if you want to multiply your efforts and achieve high levels of success. Six of the most powerful techiques possible are dramatised for your supervisors to assure co-operation is fast and unquestioned every time they need something done. It shows not only how to build employee's confidence in the supervisor, but how the supervisor can use their co-operation to lighten supervisory work loads through delegation and use of team training techniques.
Keywords: Delegation of authority; Supervision of employees